The effect of postgraduate training in smoking cessation care on the clinical practice of pulmonologists - Pinar Bostan; Banu Salepci; Mehmet A. Uysal (Tobacco Induced Diseases, 2023)
Introduction Many studies have shown that training in smoking cessation care (SCC) is important for increasing the number and quality of delivered interventions by health professionals, and various training methods are available. The study aimed to identify the relationship between receiving training on SCC and the frequency of providing outpatient-based SCC among pulmonologists who were members of the Turkish Thoracic Society (TTS).